2022
DOI: 10.19094/contextus.2022.71500
|View full text |Cite
|
Sign up to set email alerts
|

Quality of telework life, job crafting, and work well-being of public school teachers in the Federal District

Abstract: This study tested the impacts of perceptions of quality of telework life and job crafting on public school teachers’ work well-being. The sample was composed of 184 teachers who answered a questionnaire with scales previously validated in Brazil. Confirmatory factor analysis and structural equation modeling were performed. Perceptions of quality of telework life and job crafting actions predicted work well-being and contributed to investigating gaps in the organizational and work literature. This study offers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
0
3
0
5
Order By: Relevance
“…O trabalho remoto foi objeto de estudo em diferentes setores, como no setor público (Leite & Lemos, 2021); no ensino docente superior privado (Silva et al, 2021a); em escolas públicas no Distrito Federal (Paschoal et al, 2022); ou no setor de seguradoras (Carlos, 2021). Do ponto de vista dos trabalhadores das empresas que migraram para o modelo remoto, foram observados relatos nas pesquisas realizadas sobre a desigualdade de condições entre os funcionários para exercerem as suas atividades profissionais.…”
Section: A Implantação Do Home Officeunclassified
See 1 more Smart Citation
“…O trabalho remoto foi objeto de estudo em diferentes setores, como no setor público (Leite & Lemos, 2021); no ensino docente superior privado (Silva et al, 2021a); em escolas públicas no Distrito Federal (Paschoal et al, 2022); ou no setor de seguradoras (Carlos, 2021). Do ponto de vista dos trabalhadores das empresas que migraram para o modelo remoto, foram observados relatos nas pesquisas realizadas sobre a desigualdade de condições entre os funcionários para exercerem as suas atividades profissionais.…”
Section: A Implantação Do Home Officeunclassified
“…As dificuldades para as mulheres no equilíbrio de tarefas familiares, domésticas e profissionais agravaram a situação de stress e esgotamento emocional das mesmas. Em abordagem semelhante sobre o impacto do home office para as mulheres, Paschoal et al (2022) indicaram evidências sobre a qualidade de vida no trabalho e bem-estar de docentes da rede pública do Distrito Federal, e os resultados apontaram a abrangência de fatores e variáveis presentes na adaptação dos profissionais ao trabalho remoto, incluindo questões tecnológicas, familiares e psicológicas.…”
Section: A Implantação Do Home Officeunclassified
“…Existing studies have explored several aspects of teleworking on teachers’ physical and mental health ( Barros, 2017 ), family harmony ( Paschoal et al, 2022 ), work engagement ( Lewig and Metzer, 2007 ), job satisfaction ( Gu et al, 2020 ), and job well-being ( Gajendran and Harrison, 2007 ), the results of the study showed different effects depending on the region, environment, and group. However, the effect of teleworking on teachers’ social anxiety has not received the attention it deserves, and there are almost no relevant studies.…”
Section: Introductionmentioning
confidence: 99%
“…O avanço de inovações das tecnologias de informação e comunicação demandam a compreensão da relação entre as atividades de trabalho e a dinâmica das vivências dos trabalhadores que operam nas organizações (PAS-CHOAL; SILVA; DEMO;FOGAÇA;FERREIRA, 2022). Considerando a inovação como uma ideia prática ou objeto percebido como novo pelo indivíduo (ROGERS, 2003), o uso de tecnologias digitais na educação pode ser considerado como uma inovação.…”
Section: Introductionunclassified